Framing Analysis In Media Television News MetroTVOne Related Arrest by the Chairman MK Akil Mocktar Commission Case of Corruption - Aryadi, Aryadi (Jurnal The Messenger, 2014)
Aryadi, G331.10.0018.Framing  Analysis In Media Television News Metro TVOne Related Arrest by    the    Chairman    MK  Akil     Mocktar    Commission    Case    of  Corruption    Skripsi    :  Program    S1    of Communication University of Semarang.This research aims to understand how the framing of television-related  news in the arrest of thechairman of the Constitutional Court AkilMocktar by the Commission on cases of corruption. Impressions is catching   news MK chairman  AkilMocktar  on Metro TV and TVOne. Theoretical  foundation,   framing analysis model of Murray Edelman, the theory is used to understand the reality of diverse and irregular into a reality that has meaning, using the categorization, the use of a particular perspective with certain words is also a word that signifies how the facts or reality understood.Qualitative research methods and strategies for framing the analysis, the study was conducted by observing the video sempel news on Metro TV and TVOne selected.Based on the research results, the general conclusion of each media that Metro TV and TVOne has a different way of constructing a bribery case Mocktar chairman MK Akil is in its message. Metro TV tend to highlight cases of bribery Court of facts, Metro TV does not describe the alleged emerging society. While TVOne looks construct audiences with growing allegations in the news